The improvement and testing of Musa: a global partnership: Proceedings of the First Global Conference of the International Musa Testing Program, 27-30 April 1994, La Lima, Honduras - Jones, D.R. (1994)
Following an introduction to the INIBAP International Musa Testing Program (IMTP), papers on banana and plantain improvement presented at this conference are grouped into 5 sections: target diseases of the IMTP Phase II (4 papers), germplasm transfer (3), conventional breeding for disease resistance (6), mutation breeding for disease resistance (7), and training (1). Technical guidelines for IMTP Phase II, acronyms and abbreviations, and a list of participants are appended. (Abstract © CAB ABSTRACTS, CAB International)